2011
DOI: 10.1016/j.seizure.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Disease duration and arcuate fasciculus abnormalities correlate with psychoticism in patients with epilepsy

Abstract: Long disease duration and impairment of arcuate fasciculus integrity may predispose the development of psychoticism in patients with epilepsy. Our results provide important insights into the pathophysiological mechanisms underlying personality change in epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Full text was screened in 71 cases and reference lists were inspected to detect additional studies not identified with the initial search. Forty-two studies met the inclusion criteria for the meta-analysis (Ahmadi et al, 2009, Andrade et al, 2014, Arfanakis et al, 2002, Braakman et al, 2014, Campos et al, 2015, Concha et al, 2005, Concha et al, 2007, Concha et al, 2009, Deppe et al, 2008, Diao et al, 2015, Diehl et al, 2008, Duning et al, 2010, Gao et al, 2012, Govindan et al, 2008, Gross et al, 2006, Holt et al, 2011, Hutchinson et al, 2010, Keller et al, 2011, Keller et al, 2012, Kemmotsu et al, 2011, Kemmotsu et al, 2014, Kim et al, 2011, Knake et al, 2009, Kori et al, 2013, Labate et al, 2015, Lee et al, 2013, Lee et al, 2014, Li et al, 2010, Liacu et al, 2012, Lin et al, 2008, Liu et al, 2011, Mao et al, 2011, McDonald et al, 2008, Meng et al, 2010a, Nilsson et al, 2008, Powell et al, 2007, Pustina et al, 2015, Rodrigo et al, 2007, Scanlon et al, 2013, Vulliemoz et al, 2011, Wang et al, 2010, Xiao et al, 2014). The total number of people with epilepsy and controls was 1027 and 1122, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Full text was screened in 71 cases and reference lists were inspected to detect additional studies not identified with the initial search. Forty-two studies met the inclusion criteria for the meta-analysis (Ahmadi et al, 2009, Andrade et al, 2014, Arfanakis et al, 2002, Braakman et al, 2014, Campos et al, 2015, Concha et al, 2005, Concha et al, 2007, Concha et al, 2009, Deppe et al, 2008, Diao et al, 2015, Diehl et al, 2008, Duning et al, 2010, Gao et al, 2012, Govindan et al, 2008, Gross et al, 2006, Holt et al, 2011, Hutchinson et al, 2010, Keller et al, 2011, Keller et al, 2012, Kemmotsu et al, 2011, Kemmotsu et al, 2014, Kim et al, 2011, Knake et al, 2009, Kori et al, 2013, Labate et al, 2015, Lee et al, 2013, Lee et al, 2014, Li et al, 2010, Liacu et al, 2012, Lin et al, 2008, Liu et al, 2011, Mao et al, 2011, McDonald et al, 2008, Meng et al, 2010a, Nilsson et al, 2008, Powell et al, 2007, Pustina et al, 2015, Rodrigo et al, 2007, Scanlon et al, 2013, Vulliemoz et al, 2011, Wang et al, 2010, Xiao et al, 2014). The total number of people with epilepsy and controls was 1027 and 1122, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies the temporal onset of seizures was confirmed by seizure recordings. We excluded several other DTI studies in people with epilepsy (Thivard et al., 2005; Powell et al., 2007; Focke et al., 2008; Yogarajah et al., 2008; Schoene‐Bake et al., 2009; Bhardwaj et al., 2010; Liacu et al., 2010; Liao et al., 2010; Riley et al., 2010; Afzali et al., 2011; Holt et al., 2011; Mao et al., 2011), because of heterogeneity in the patient group, postoperative instead of preoperative DTI, or different processing of white matter (e.g., voxel‐based analysis).…”
Section: Resultsmentioning
confidence: 99%
“… Sundram et al (2012) reported that antisocial personality disorder ( n = 30: 15 cases, 15 controls)—which in turn is linked to low agreeableness and low conscientiousness ( Lynam and Widiger, 2001 )—was negatively associated with FA in several regions, including the genu of the corpus callosum and the right uncinate fasciculus. Finally, Mao et al (2011) reported that psychoticism measured using the Eysenck Personality Questionnaire—which is noted to be a combination of agreeableness and conscientiousness (e.g. McCrae and Costa, 1985 )—was related to FA in the arcuate fasciculus ( r = −0.29, −0.36: L/R hemisphere, respectively) in a sample of patients with epilepsy ( n = 65); no significant correlations with neuroticism or extraversion were observed.…”
Section: Introductionmentioning
confidence: 98%